Designing a Strategic Model Based on Succession Planning in Gymnastics in Iraq - Al-Khafaji, Haider A; Seifari, Masoumeh Kalateh (مجلة دراسات وبحوث التربية الرياضية, 2024)
This research aims to develop a strategic succession planning model in the sport of gymnastics in Iraq. The research, from an applied perspective, utilizes descriptive-analytical methods and, in terms of execution method, employs qualitative research. The data for this research were gathered through semi-structured interviews and sampling was done purposefully using the Strauss and Corbin method. Among all managers and stakeholders in gymnastics across Iraq, a total of 11 individuals were selected for the interviews based on theoretical saturation. The interviews were analyzed using interpretive analysis techniques, open coding, axial coding, and selective coding. The analysis of the interviews identified the conditions for succession planning, including human resource management, talent management, support programs, and efficiency enhancement. The contextual and organizational factors influencing succession planning (strategic succession), the conditions for intervention (individual factors), strategies (creating a succession system and individual evaluation), and the consequences (individual and organizational development) were explored. The findings of the interview analysis indicate that strategic succession planning in Iraqi gymnastics can lead to a sense of belonging and development efforts, strengthening the workforce, and using the experiences of veterans to enhance the stability and sustainability of gymnastics in Iraq.